Japanizität aus dem Geist der europäischen Romantik - Morikawa, Takemitsu (Lettre, 2013)
After the opening of the country in the middle of the 19th century, Japan quickly moved towards becoming an industrialized world power. But the romanticist syndrome, imported from Europe by Mori Ogai since the 1890s, especially enchanted young intellectuals and drove their search of a Japanese cultural identity. The goal was, internally, to integrate the entire population, and externally, to make the country distinguishable from the »West« ─ paradoxically, in a spirit of European Romanticism. Takemitsu Morikawa investigates these remarkable developments and retraces the rise and canonization of the alleged self-image of modern Japan.